2010
DOI: 10.1177/0748233710364966
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions changes among Egyptian sewage network workers

Abstract: The current work aimed at investigating the cognitive functions impairment among workers of sewer networks due to exposure to hydrogen sulfide (H(2)S) and the relation of this impairment, if any, to the level of H(2)S exposure biomarker 'urinary thiosulfate.' Besides, the validity of using Mini Mental State Examination (MMSE) as screening test for cognitive impairment among the exposed workers was tested. The work was conducted among 33 sewage network maintenance male workers and a matched unexposed control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Most other H 2 S studies with cognitive function tests have involved occupationally or industrially exposed populations (De Fruyt et al, 1998, Farahat and Kishk, 2010, Kilburn, 1997) where H 2 S exposure can be difficult to quantify. Some used duration of H 2 S exposure, rather than H 2 S measurements (Kilburn, 1997, 2003), while others reported few measurements (Kilburn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most other H 2 S studies with cognitive function tests have involved occupationally or industrially exposed populations (De Fruyt et al, 1998, Farahat and Kishk, 2010, Kilburn, 1997) where H 2 S exposure can be difficult to quantify. Some used duration of H 2 S exposure, rather than H 2 S measurements (Kilburn, 1997, 2003), while others reported few measurements (Kilburn et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the range of symptoms are also broad, extending from central nervous system (CNS), respiratory, and gastrointestinal symptoms to infection and flu-like symptoms (Lundholm and Rylander, 1983, Melbostad et al, 1994, Douwes et al, 2001, Thorn et al, 2002, Heldal et al, 2010. Of all the airborne exposure associated with handling waste water at sewage treatment plants, hydrogen sulphide (H2S) from degradation of organic material in the sewage and endotoxins from Gram-negative bacteria are of particular interest (Adelson and Sunchine, 1966, Beauchamp et al, 1984, Latinen et al, 1994, Farahat and Kishk, 2010. High-dose acute exposure to H2S can be extremely hazardous, being able to cause pulmonary oedema (> 300 ppm) and sudden unconsciousness (> 500 ppm) or death by even a single exposure at levels above 1,000 ppm (NEG 2001).…”
Section: Introductionmentioning
confidence: 99%
“…High-dose acute exposure to H2S can be extremely hazardous, being able to cause pulmonary oedema (> 300 ppm) and sudden unconsciousness (> 500 ppm) or death by even a single exposure at levels above 1,000 ppm (NEG 2001). However, repeated exposure to low levels of H2S (1-10 ppm) may possibly result in chronic symptoms from the CNS, such as fatigue, headache, poor memory and concentration difficulties (Tvedt et al, 1991, Richardson, 1995, Watt et al, 1997, Lee et al, 2007, Farahat and Kishk, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…WWWs commonly suffer from various health symptoms, including neurological and respiratory tract [ 1 5 ]. These effects have been ascribed to exposure to microorganisms and noxious gases such as H 2 S or from exposure to low levels of different biological and chemical agents [ 1 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular H 2 S exposure has been associated with cognitive impairment among WWWs [ 5 ] and neurological symptoms [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%